Enhanced physical and photoelectrochemical properties of Bi2S3 nanorod films via indium doping - Radhalayam, D (Elsevier Ltd, 2026)
Bismuth sulfide (Bi2S3) is a promising material for photoelectrochemical (PEC) water splitting, but its performance is limited by poor charge transport and high electron–hole recombination. This study reports the enhancement of the physical and PEC performance of Bi2S3 photoelectrodes through the synthesis of indium (In)-doped nanorod films via a seed-layer-assisted chemical bath deposition method. Utilizing an Sb2S3 seed-layer-assisted growth approach, the films were doped with In concentrations ranging from 0.14 to 0.25 at.%. X-ray diffraction analysis confirmed improved crystallinity, with the crystallite size increasing from 15.2 nm (pristine) to 38.1 nm (In-doped). Field emission scanning electron microscopy revealed a remarkable enhancement in nanorod density, vertical alignment, and size, with lengths increasing from 50–100 nm (pristine) to over 200 nm (In-doped). Optical studies demonstrated a reduced energy gap from 1.23 eV (pristine) to 1.05 eV (In-doped), enhancing light absorption. PEC testing showed a dramatic increase in photocurrent density, from 4.5 mA/cm2 for Bi2S3 to 10.0 mA/cm2 for the seed-layer-grown film, and further to 12.0 mA/cm2 at 1 V vs. Ag/AgCl for the In-doped films. Electrochemical impedance spectroscopy revealed reduced charge transfer resistance in the doped films, indicating better charge separation and collection. Stability testing confirmed superior photocurrent retention in In-doped films, highlighting their resistance to degradation and photocorrosion. These results underscore the synergistic benefits of seed-layer growth and In doping in enhancing the physical properties and PEC performance of Bi2S3 films. The In-doped Bi2S3 photoelectrodes exhibit exceptional PEC performance, making them promising candidates for solar-driven water splitting and other energy-conversion applications. © 2025 The Authors.